Management of Kleptomania in Children: A Case Report - Yusri Hapsari Utami (Scientia Psychiatrica, 2021)
Introduction. Kleptomania is a disorder characterized by the repeated inability to resist the urge to steal / take other people's things. Items that are taken are usually only small items and are not needed. The impulsive urge to take the item is often accompanied by anxiety disorders, or depressive disorders. This case report aims to present cases of kleptomania in children and their management. Case Presentation. a 14 years old girl, a junior high school student, middle socioeconomic background, lived in a suburban area of Jakarta, came to consult a psychiatric polyclinic with complaints that she could not resist the urge to steal other people's things without purpose, and without being planned before. The patient behaves mostly when she is sad or anxious when he remembers the argument between his parents. According to the patient, her parents often quarrelled for economic reasons. Conclusion.Combination of medication and cognitive behaviour therapy is effective in kleptomania treatment. Supportive family environment encourage patient’s recoveryfrom kleptomania.